The Role of Fear of Loss of Vigilance and Reexperiencing in Insomnia Among Veterans. (1st October 2016) - Hull, Amanda; Holliday, Stephanie Brooks; Reinhard, Matthew; Kobayashi, Ihori; Mellman, Thomas
ABSTRACT: This study examined the relationship between sleep fears and insomnia in veterans. Participants completed questionnaires assessing mental health, pain, insomnia, and sleep fears. Most veterans (84.54%) endorsed clinically significant insomnia. Veterans with a history of combat zone deployment and who screened positive for possible post-traumatic stress disorder (PTSD) reported more insomnia symptoms, and both factors were associated with increased fear of reexperiencing and losing vigilance. Regression analyses indicated that fear of reexperiencing and losing vigilance were associated with insomnia severity, controlling for depression, pain, and possible PTSD. These results suggest the importance of assessing and targeting these cognitions when treating veterans with insomnia.